(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2021)
The technology (IOT) is a huge influx of technological advancements (ICT). The Iot technology (IoT) is a broad phrase that encompasses a wide range of capabilities, possible uses, multiple data collection, and operating approaches. The present IOT research activities are centered on the creation but also design of mandates and open infrastructures, which still have issues that must be overcome before they can be fully implemented. This paper includes an introduction of IoT technology and its uses in farming systems, as well as a measurement of prior survey research and a suggestion for an irrigation management monitoring system. This project’s main purpose is to create new agricultural technologies that will boost vegetative growth and water resources. Following the measurement of temperature, humidity, and moisture content, a smart control system is provided, which employs cutting-edge electrical tech and a microcontroller to switch the hydrostatic gear ON and OFF when the atmosphere’s most content is recognized. Following the temperature measurements, moisture levels, and soil moisture, a Bluetooth service member is also offered.